Retrieval, Monitoring, and Control Processes: A 7 Tesla fMRI Approach to Memory Accuracy - Markowitsch, Hans J.; Risius, Uda M.; Staniloiu, Angelica; Piefke, Martina; Maderwald, Stefan; Schulte, Frank; Brand, Matthias (Frontiers in Behavioral Neuroscience, 2013)
Memory research has been guided by two powerful metaphors: the storehouse (computer) and the correspondence metaphor. The latter emphasizes the dependability of retrieved mnemonic information and draws upon ideas about the state dependency and reconstructive character of episodic memory. We used a new movie to unveil the neural correlates connected with retrieval, monitoring and control processes, and memory accuracy (MAC), according to the paradigm of Koriat and Goldsmith (1996a, b). During functional magnetic resonance imaging, subjects performed a memory task which required (after an initial learning phase) rating true and false statements (retrieval phase, RP), making confidence judgments in the respective statement (monitoring phase, MP) and deciding for either venturing (volunteering) the respective answer or withholding the response (control phase, CP). Imaging data pointed to common and unique neural correlates. Activations in brain regions related to RP and MAC were observed in the precuneus, middle temporal gyrus and left hippocampus. MP was associated with activation in the left anterior and posterior cingulate cortex along with bilateral medial temporal regions. If an answer was volunteered (as opposed to being withheld) during the CP, temporal and frontal as well as middle and posterior cingulate areas and the precuneus revealed activations. Increased bilateral hippocampal activity was found during withholding compared to volunteering answers. The left caudate activation detected during withholding compared to venturing an answer supports the involvement of the left caudate in inhibiting unwanted responses. Contrary to expectations, we did not evidence prefrontal activations during withholding (as opposed to volunteering) answers). This may reflect our design specifications, but alternative interpretations are put forth.